STRATEGI BERSAING DALAM BERBISNIS SECARA ISLAMI - Utari Cahyani (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Strategy is a way to achieve an objective in our business. Business objective are generally for gain profit and to get capital. It is necessary to have competitive strategy in our business so we have competitive advantage compare to another corporation. There are three competitive strategy that is suggested by Porter. They are cost leadership, differentiation, and focus. On another hand, Mintzberg suggest two competitive strategy - differentiation and not differentiated. Islam also teach us about competitive strategy in doing our business. Three point that we have to concern when we discuss about business competition in Islamic point of view: every actors that involve in certain business, how to compete, and products that are competed by industry.